A value clarification on quality within Nursing Colleges in Gauteng - S. Armstrong; M. Muller (AOSIS, 2002)
Quality assurance in higher education has been legislated. It is therefore necessary to develop a quality audit system for Nursing Colleges in Gauteng. The process of developing such a system is complex and needs to foster ownership by all the stakeholders. The first step in this process is to conduct a value clarification on quality. The purpose of this article is to explore and describe a value clarification on quality within the Nursing Colleges in Gauteng. An explanatory and descriptive qualitative research design was utilised. The results are grouped into structure, process and outcome values. Comparisons between the views of the different role-players are also presented. It is recommended that these results be utilised as the basis of a conceptual framework for the quality audit system for Nursing Colleges in Gauteng, as well as the development of quality indicators for Nursing Education Institutions in South Africa.